Evaluation of the Accuracy of Conventional and Digital Impression Techniques for Implant Restorations - Moura, Renata Vasconcellos; Kojima, Alberto Noriyuki; Saraceni, Cintia Helena Coury; Bassolli, Lucas; Balducci, Ivan; Özcan, Mutlu; Mesquita, Alfredo Mikail Melo (My University, 2018)
Purpose: The increased use of CAD systems can generate doubt about the accuracy of digital impressions for angulated implants. The aim of this study was to evaluate the accuracy of different impression techniques, two conventional and one digital, for implants with and without angulation. Materials and Methods: We used a polyurethane cast that simulates the human maxilla according to ASTM F1839, and 6 tapered implants were installed with external hexagonal connections to simulate tooth positions 17, 15, 12, 23, 25, and 27. Implants 17 and 23 were placed with 15° of mesial angulation and distal angulation, respectively. Mini cone abutments were installed on these implants with a metal strap 1 mm in height. Conventional and digital impression procedures were performed on the maxillary master cast, and the implants were separated into 6 groups based on the technique used and measurement type: G1 - control, G2 - digital impression, G3 - conventional impression with an open tray, G4 - conventional impression with a closed tray, G5 - conventional impression with an open tray and a digital impression, and G6 - conventional impression with a closed tray and a digital impression. A statistical analysis was performed using two-way repeated measures ANOVA to compare the groups, and a Kruskal-Wallis test was conducted to analyze the accuracy of the techniques. Results: No significant difference in the accuracy of the techniques was observed between the groups. Therefore, no differences were found among the conventional impression and the combination of conventional and digital impressions, and the angulation of the implants did not affect the accuracy of the techniques. Conclusions: All of the techniques exhibited trueness and had acceptable precision. The variation of the angle of the implants did not affect the accuracy of the techniques.
Keywords: Angulated implants; CAD; Dental impression